2004
DOI: 10.1038/sj.leu.2403552
|View full text |Cite
|
Sign up to set email alerts
|

Induction of gene expression by 5-Aza-2′-deoxycytidine in acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) but not epithelial cells by DNA-methylation-dependent and -independent mechanisms

Abstract: The methylation inhibitor 5-Aza-2 0 -deoxycytidine (5-Aza-CdR, decitabine) has therapeutic efficacy in acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). Using microarray analysis, we investigated global changes in gene expression after 5-Aza-CdR treatment in AML. In the AML cell line OCI-AML2, Aza-CdR induced the expression of 81 out of 22 000 genes; 96 genes were downregulated (X2-fold change in expression). RT-PCR analysis of 10 randomly selected genes confirmed the changes of expression in AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
79
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 34 publications
13
79
1
1
Order By: Relevance
“…6). Similar DNA methylationindependent gene inactivation, which can be activated by 5-Aza CdR, was reported in mouse centromeric heterochromatin (Takebayashi et al, 2001) and acute myeloid leukemia cells (Schmelz, Sattler, Wagner, Lubbert, Dorken, & Tamm, 2005). Treatment of CHO cells with both agents shows only an additive effect on the increase of the amounts of acetylated histone H3.…”
Section: Discussionsupporting
confidence: 72%
“…6). Similar DNA methylationindependent gene inactivation, which can be activated by 5-Aza CdR, was reported in mouse centromeric heterochromatin (Takebayashi et al, 2001) and acute myeloid leukemia cells (Schmelz, Sattler, Wagner, Lubbert, Dorken, & Tamm, 2005). Treatment of CHO cells with both agents shows only an additive effect on the increase of the amounts of acetylated histone H3.…”
Section: Discussionsupporting
confidence: 72%
“…Surprisingly, the administration of 5AC alone was associated with induction of acetylated histones H3 and H4 in 11/23 evaluable patients. Coupled with recent studies suggesting that DAC can induce expression of unmethylated genes such as CDKN2D and p21 WAF1/CIP1 (Zhu et al, 2001;Schmelz et al, 2005a), these data indicate that molecular mechanisms in addition to the reexpression of methylated genes may contribute to the clinical activity of DNMT inhibitors. This study examines the induction of the expression of the unmethylated cell cycle regulatory gene p21 WAF1/CIP1 (Brakensiek et al, 2005;Scott et al, 2006) in response to the DNMT inhibitor DAC.…”
Section: Introductionsupporting
confidence: 63%
“…In this study, we observed a synergistic upregulation of p21 WAF1/CIP1 by DAC and HDAC inhibitors despite the unmethylated status of its promoter. Recent studies indicated that decitabine (DAC) can induce regional chromatin remodeling of other unmethylated genes, including RPGR, CD14, PTPN22 and calgranulin, which could explain the above-mentioned synergy (Schmelz et al, 2005a). However, the synergistic interaction between DNMT and HDAC inhibitors may stem from other potentially non-epigenetic mechanisms in addition to the inhibition of HDAC recruited directly by methyl-binding proteins to methylated promoters (Bird and Wolffe, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-1 can be reactivated by both DAC and TSA alone, through increasing ICAM-1 promoter histone H3 acetylation and H3 Lys 4 methylation. Increased histone acetylation, H3 Lys 4 methylation, and/or gene expression by DNMT inhibitors independently of effects on DNA methylation have been described before (38)(39)(40). The potency of the DNMT inhibitors DAC and zebularine to reactivate ICAM-1 independently of promoter DNA methylation indicates that methylation-independent silencing activity of DNMTs might be essential for ICAM-1 down-regulation in tumor endothelial cells.…”
Section: Discussionmentioning
confidence: 99%